Age-related changes in the quadriceps tendon: Collagen fibril diameter decreases with aging - Yoshihiro Ishida; Yasushi Takata; Tatsuya Ishikawa; Mitsuhiro Kimura; Naoki Takemoto; Manase Nishimura; Noriyuki Ozaki; Satoru Demura; Junsuke Nakase (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
Background: The quadriceps tendon (QT) has recently gained attention as a graft tendon for anterior cruciate ligament (ACL) reconstruction due to its high strength from a larger ultrastructural collagen fibril diameter in children than that of the semitendinosus tendon. While QT collagen fibril diameter increases with growth, changes in older adults remain unclear. This study investigated age-related changes in QT collagen fibril diameter. Methods: Twenty-four patients who had undergone ACL reconstruction using the QT or other knee surgeries were included. QT tissues collected during surgery were analyzed using transmission electron microscopy. Collagen fibril diameter was measured in four groups: Immature (11–13 years), Young (15–17 years), Adult (21–50 years), and Older (61–81 years). The average fibril diameter was calculated for each sample. At least four slides (one slide = one digital electron micrographs of the ultrathin section) were evaluated for each specimen, with at least 200 collagen fibrils on each slide. The average number of collagen fibrils measured per specimen was 812 ± 10. Data of the four groups were analyzed using one-way analysis of variance and Tukey's test. Results: The mean collagen fibril diameters were 89.7 ± 14.4, 94.8 ± 16.4, 107.2 ± 12.1, and 73.0 ± 9.7 nm in the Immature, Young, Adult, and Older groups, respectively. Although no significant difference was observed between the Immature and Young groups, fibril diameter was significantly larger in the Adult group than in the Young group and significantly smaller in the Older group than in the other groups. Conclusions: The average QT collagen fibril diameter increased with growth but was lower in the Older group, suggesting a decrease with aging.